The veiled God : Friedrich Schleiermacher's theology of finitude - Jackson Ravenscroft, Ruth (Studies in Systematic Theology, 2019)
In The Veiled God , Ruth Jackson Ravenscroft offers a detailed portrait of Friedrich Schleiermacher's early life, ethics, and theology in its historical and social context. She also critically reflects on the enduring relevance of his work for the study of religion. The book analyses major texts from Schleiermacher's early work. It argues that his experiments with literary form convey his understanding that human knowledge is inherently social, and that religion is thoroughly linguistic and historical. The book contends that by making finitude (and not freedom) a universal aspect to human life, Schleiermacher offers rich conceptual resources for considering what it means to be human in this world, both in relations of difference to others, and in relation to the infinite.